Pendidikan Inklusif Multikultural Perspektif Hadis - Damanhuri; M. Zainal Arifin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Research on social interaction has always been an important topic of study because good social interaction is the basis for building peace between different religions, races and cultures. This research aims to discuss hadiths that explain inclusive attitudes.The formal object in this research is the science of hadith, while the material object is the hadith about openness or tolerance narrated by Imam Muslim. Results of this researchis that the status of the hadith regarding an inclusive attitude of ṣahih quality with the qualification maqbul ma'mul bih for the experience of religious communities as a form of closeness. The conclusion of this research isMuslim historical hadiths are relevant to be used as a reference for the world of education in Indonesia towards inclusive and tolerant education.